ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN REGULASI DIRI DALAM UPAYA PENCEGAHAN PERILAKU MEROKOK PADA SISWA SMP - Nisa` Muhibaturrohmah, Chotrun; Nuryono, Wiryo; Winingsih, Evi; Purwoko, Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Self-regulation is an individual’s ability to manage their thoughts, emotions, and behavior in a purposeful manner to achieve positive goals. This ability is crucial for adolescents in coping with social pressures and avoiding risky behaviors such as smoking. This study aims to analyze the need for educational media to enhance self-regulation as a preventive measure against smoking behavior among junior high school students. The study employed a Research and Development (R&D) approach using the ADDIE model, limited to the needs analysis phase. The study subjects included 112 eighth-grade students and guidance and counseling teachers at a junior high school in Surabaya. Data were collected through questionnaires and interviews. The results indicated that students demonstrated a reasonably good level of self-regulation regarding the dangers of smoking; however, they still require more engaging and interactive educational media. Therefore, the development of technology-based media such as Augmented Reality and game-based learning has the potential to support guidance and counseling services in enhancing students’ self-regulation as a preventive measure against smoking behavior.